9=7x+-6

Simple and best practice solution for 9=7x+-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9=7x+-6 equation:



9=7x+-6
We move all terms to the left:
9-(7x+-6)=0
We add all the numbers together, and all the variables
-(7x-6)+9=0
We get rid of parentheses
-7x+6+9=0
We add all the numbers together, and all the variables
-7x+15=0
We move all terms containing x to the left, all other terms to the right
-7x=-15
x=-15/-7
x=2+1/7

See similar equations:

| 113xx=75-1 | | 31=3(7-2x) | | -(n-7)-4n=10-4n | | 3-0.25=-1/2x+9 | | 2/5g-7=15 | | 2.x-6=10 | | 30x+50=C | | -9/8=-3b+9/4b | | 3(3x-4)=-(4x+7) | | 31=21-6x | | 36+4+3x=2x-13 | | x+4=1/ | | 42+-21x+12x=44 | | 5-7y-2y+4+3y=-20 | | 5+7y-2y+4+3y=-20 | | 57y-2y+4+3y=-20 | | 3+(n/5)=5 | | 30x+50=260 | | W2+2w-24=0 | | Y=40-3y | | 30(8.75+11t=400 | | 1.35x=64.00 | | -21x+54=44 | | -3(2x-8)=4(x-4) | | 60=40x-5x^2 | | 4-2s/3=5 | | 2(3x+4)+2=+4+3x | | -8=-x/4 | | -106=3p-8(-7-3p) | | +2(x+7)=14x–7 | | 0.1÷1=0.2÷x | | 10/19=18/x |

Equations solver categories